Australian nurses' perceptions of the use of manual restraint in the Emergency Department: A qualitative perspective - Chapman, Rose; Ogle, K.; Martin, C.; Rahman, A.; Mckenna, B.; Barnfield, J. (Wiley-Blackwell Publishing, 2016)
Aims and objectives: To explore emergency nurses perceptions of the use of manual restraint. Background: Manual restraint of patients has historically been an accepted practice, though little is known about the use of manual restraint in general hospitals. Design: A qualitative, descriptive, exploratory, study was undertaken. Method: Fifteen semi-structured interviews with emergency nurses were completed. Data were analysed using qualitative thematic analysis procedures. Results: The following themes were identified: 'part of the job', 'reasons for manual restraint', 'restraint techniques', 'consequences' and 'lack of documentation'. Manual restraint occurred frequently each shift and most were not documented. This may be due to nurse's perceptions that manually restraining a patient did not comprise formal restraint and was the only option. Nurses used manual restraint to manage patients who were violent and aggressive or to perform procedures. However, they reported a lack of education and training in manual restraint. Nurses identified several consequences for the patient, staff and the organisation as a result of these events including psychological and physical injuries. Conclusions: Empirical research of prevalence and issues surrounding manual restraint events is required to inform health care organisations and government to develop, implement and evaluate appropriate policies and strategies to ensure safety of patients and staff. The employment of peer support workers and professionals with expertise in mental health and dementia may aid in the reduction of manual restraint events and improve care of all patients within the Emergency Department. Research on manual restraint in health settings is also needed. Relevance to clinical practice: Nurses need to be aware that manual restraint is not just an accepted part of their work, but is a strategy of last resort that should be documented. Organisations must implement standardised educational programmes for nurses together with policies and processes to monitor and evaluate manual restraint events.